Upaya Penanaman Nilai-Nilai Kearifan Lokal dalam Pembelajaran Sejarah: Studi Kasus MAN 1 Mandailing Natal - Siregar, Andre Syahbana; Rusydah, Imroatur (Education & Learning, 2024)
Education is not only focused on understanding the material but also on shaping attitudes and utilizing media to preserve local culture. The importance of instilling local wisdom as a means for students to better understand and cherish their culture. This qualitative research adopts a narrative approach, involving history teachers and students from MAN 1 Mandailing Natal as informants. Data collection is carried out through observation, interviews, and documentation, with data validity tested using triangulation of techniques and sources. Data analysis involves interaction analysis, encompassing data collection, reduction, presentation, and conclusions. The research findings indicate that the cultivation of local wisdom by teachers primarily relates to local culture, while the implementation of local wisdom values by students has been successful, covering ethical, aesthetic, religious, and social aspects.